1999
DOI: 10.1046/j.1523-1739.1999.97471.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pollinator Loss on Endemic New Zealand Mistletoes (Loranthaceae)

Abstract: The endemic mistletoes Peraxilla colensoi and P. tetrapetala (Loranthaceae) have declined considerably in New Zealand since 1840, reputedly because of introduced herbivores but coincident with a major decline in native bird densities. We show that at two South Island sites ( Craigieburn and Ohau) there are too few bird pollinators visiting the flowers to allow full fruit set. We studied pollination rates in P. colensoi at Wakefield and P. tetrapetala at Craigieburn over four flowering seasons and P. tetrapetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 42 publications
3
90
1
Order By: Relevance
“…Declines in pollination (24) and seed dispersal (20) as a result of bird extinctions may lead to extinctions of dependent plant species (25). The former is particularly important in the Austral, New Zealand, and Oceanic regions, where the proportion of bird-pollinated plants is higher than other parts of the world (26), and, in the case of the latter two regions, most of the presettlement avifauna is already extinct (27).…”
Section: Discussionmentioning
confidence: 99%
“…Declines in pollination (24) and seed dispersal (20) as a result of bird extinctions may lead to extinctions of dependent plant species (25). The former is particularly important in the Austral, New Zealand, and Oceanic regions, where the proportion of bird-pollinated plants is higher than other parts of the world (26), and, in the case of the latter two regions, most of the presettlement avifauna is already extinct (27).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to do this suggest that the presence of a third species (predator or competitor) may stabilize some mutualistic interactions [3]. The persistence of assemblages of several pollinator species is important in the context of the conservation of biodiversity [36,37]. It has been shown that there is a relation between pollination and the plant reproductive success, as well as a relation between pollinator's visits and the flowers' nectar offer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Data in O'Donnell and Dilks (1994) were presented as percentages by columns (birds); we multiplied up to counts, then calculated percentages by rows (plants), excluding plants with fewer than 10 observations. Our own data were obtained either by direct or video observation of groups of plants during the flowering or fruiting season (see Robertson et al 1999 for details). The data presented here are the proportion of visits made for site-species combinations.…”
Section: Approachmentioning
confidence: 99%